Pengaruh Ketebalan Chip Umbi Porang (Amorphophallus oncophyllus Prain) Terhadap Hasil Penepungan Menggunakan Hammer Mill - Gustina, Risma; Warji, Warji; Tamrin, Tamrin; Kuncoro, Sapto (abe.fp.unila.ac.id, 2022)
Flouration of porang tuber chips is one of the efforts to extend the shelf life and is one way to facilitate the processing of food made from porang tubers. The method in this study was porang chip flouring with a thickness of 1, 3, and 5 mm using a hammer mill with clearance distance of 15, 10, and 5 mm. The flouring process for porang tuber chips was repeated 3 times for each thickness with a weight of 1 kg each. The purpose of this study was to determine the effect of the thickness of the porang tuber chip and the distance between the tip of the hammer mill hammer with a sieve (clearance) on the milling time and working capacity of the pulverizing machine and analyze the uniformity index and degree/modulus of fineness resulting from the milling. The results in this study are the thickness of the porang tuber chip and the clearance distance affect the working capacity and milling results, while the uniformity index is not significantly different and the degree of fineness produced falls into the same category, namely the thicker the chip used, the longer the milling time but the results the smoother the grinding, the smaller the clearance, the less time is used for grinding and the more results milling obtained. The use of the best hammer length hammer mill is using a hammer length of 85 mm, the working capacity is greater and the results obtained are more and smoother flour and the remaining flour is also less than using a hammer length of 75 and 80 mm.